Representações sociais dos exames médicos periódicos - Fonseca, Ariana Lirio Pandini (2015)
The objective of this research was analyzing social representations in periodic medical examinations (PME) and their impact on the participation (or absence) of workers of the Federal University of Espirito Santo (UFES) in PME. In order to meet this objective, it was necessary to identify the social representations of PME for these workers, called "servidores" (in Portuguese), by listing the factors that contribute for building such representations and the reasons that interfere in the participation (or absence) at the institutional PME program. With a bibliographic review, conducted to contextualize this research, it was not possible to find studies with the same approach. Research was based on social/historical building of concepts about health and work in society and the consequences on public policies that created PME. The Theory of Social Representations (Moscovici, 2004) supported all the analysis, with the aid of important contributions from the perspective of health in the binomial biopower and bio-policy from Focault (2002). Qualitative and quantitative research was used to answer the question of research "What are the social representations of periodic examinations for the workers of Ufes and how were they built". As an instrument for research, one used documental research, which provided institutional documents related to PME and the e-questionnaire. Collected data was analyzed through descriptive statistics, concerning the quantitative aspect; concerning the qualitative aspect, the content analysis was done from the categorization of answers, according to the proposal of Baldin (2004). In the quantitative aspect, this study indicates that previous experiences with access (or lack of access) to health services, as well as the good or poor quality of these services, or the existence of negative experiences in situations related to healthcare are not relevant. Respondents who said that they do not participate in PME indicated the performance of routine examinations by themselves as the main reason for not taking part in institutional PME. Respondents who said that they take part in PME said that they do so because of concerns about their own health and institutional obligations. In qualitative analysis, the categorization, conducted in data processing, determined three categories: obligation, care and procedures. The categories obligation and care indicate an important Social Representation connected to the historical relationship between health and job. PME is understood as a way of healthcare but, at the same time, a way for the employer to control the employees. In the category procedures, it was clear that workers did not know about the proposal of the federal government about healthcare. This lack of knowledge has a significant impact on the awareness of workers about PME and, as a consequence, on their participation (or absence) in PME. This research also identified criticism and suggestions for the current structure of PME in Ufes, what made it possible to create a proposal for intervention. This study concludes that Social Representation of PME is a process that is being built in the daily routine of workers and it is very important to warn them to take part in this process, not only as workers, but also as individuals, products and producers of Social Representations.